Characterisation and fatigue of friction stir welding - Ali, Aidy; Zaroog, Omar Suliman (Suranaree University of Technology, 2008)
Previous attempts on the characterisation of Friction Stir Welding (FSW) based on microstructures, hardness, and residual stress distribution have been reviewed. The role of these parameters on fatigue damage of FSW is then discussed. Relevant conclusions have been drawn to demonstrate the current issues and the future research potential of these joints.